(Crise do) Estado Social e (in)sustentabilidade da Habitação Social. Uma leitura na Área Metropolitana de Lisboa - Pato, Isabel (2013)
The article starts by discussing the changes in the way of viewing social housing, emphasizing the importance of the “urban deprived areas” in contemporaneous urban politics. Secondly, considering statistical data, the article describes the social housing stock of Lisbon Metropolitan Area municipalities, regarding its spatial distribution and most recent evolution as well as the investment structure, focusing the analysis on the alienation of social housing stock. Additionally, the result of a survey applied to three metropolitan municipalities enables a deeper understanding of the nature of the alienation management strategy as a space- and time-discontinuous phenomenon. Thirdly it develops a critical reflection about the most recent transformations of the municipal management of the “urban deprived areas” of municipal social housing in the context of Lisbon Metropolitan Area, claiming that there are two autonomous models of intervention: one centered in the “long-distance supervising” and another one, in the opposite direction, engaged in social and urban regeneration which increases the penetration of institutional state structures in specific contexts, through “Local Project Teams”.